Desain Pelayanan Prima dengan Metode Servqual di Restoran Ikan Bakar Yayat Cilacap - Amin Syukron; Aindita Aindita (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2020)
A company's competitive advantage can be seen from how loyal consumers are to the company. one of the companies that prioritizes quality of service is restaurant, where a restaurant must be able to provide excellent service to consumers or customers. The object of this research is the Fish Grill Yayat restaurant located in the Cilacap sea turtle tourism area. by using servqual metoode, the researcher conducted a GAP search on attributes on five dimensions of service quality namely Tangiblem, Reliability, Responsiveness, Assurance, Emphaty. Based on research that has been done, there are several conclusions that can be drawn, among others, to produce a quality service product, an activity is needed to capture the expectations desired by consumers who will be translated into attributes. The greatest GAP value obtained from the results of the study is on the attributes and dimensions of Attribute 12: the quality of speed and accuracy of the services provided (-0.84), Attribute 11: the ability of employees to explain various questions clearly and easily understood language (-0, 67), Attribute 16: employee hospitality in providing services (-0.67). From these data it can be seen that the overall value of GAP 5 is negative and therefore needs to be improved.